Banking Sector Competition in Russia - Anzoategui, Diego; Martinez Peria, Maria Soledad; Melecky, Martin (2012)
The Russian banking sector includes approximately 1,000 banks, but is it competitive? This paper analyzes bank competition in Russia during 2002-2008. The authors examine indicators of concentration and contestability, and compute non-structural measures of competition. They compare competition in Russia to that in Brazil, China, and India, and contrast competition across different groups of banks within Russia. Contestability in Russia is obstructed by uneven supervisory practices and an unclear exit process. Non-structural measures reveal that banks in Russia are less competitive than those in Brazil. Within Russia, large banks and state-owned banks exert more market power than the smaller and privately-owned institutions. Finally, business-oriented banks are more competitive than those concentrating on lending to individuals.